Fairy Tale as Myth/Myth as Fairy Tale - Zipes, Jack, 1937- (Book collections on Project MUSE., 1994)
"" Explores the historical rise of the literary fairy tale as genre in the late seventeenth century. In his examinations of key classical fairy tales, Zipes traces their unique metamorphoses in history with stunning discoveries that reveal their ideological relationship to domination and oppression. Tales such as Beauty and the Beast, Snow White and the Seven Dwarves, and Rumplestiltskin have become part of our everyday culture and shapers of our identities. In this lively work, Jack Zipes explores the historical rise of the literary fairy tale as genre in the late seventeenth century and e.